(untitled) (Libyan Journal of Ecological & Environmental Sciences and Technology, 2023)
Medical waste generated from health institutions is one of the most important issues that have received great attention recently because of its negative effects on the environment and human health. This study aimed to identify the concept of medical waste management in Trahen Teaching Hospital, along with identifying the effects of this waste on workers in the health field, as well as its impact on the surrounding environment and the local community, in the subject of the study; Attributable to the variable: (gender - educational level). To achieve the objectives of the study, a measure of medical waste management was used and the necessary data were collected through the descriptive approach. The study tools were distributed to a sample of (50) male and female employees working in the health sector inside the hospital, where the study was applied to the original community of the study due to the small size of the study community. Statistical package for social sciences (SPSS) program for data analysis. The results of the study showed that: There is no appropriate system for the management of medical waste in the hospital, despite the existence of a clear understanding of the meaning of medical waste, and the risks causing it among most workers in the health sector. The results of the study also showed that there were significant differences in the average waste management measure; According to the variable (gender), most workers in health institutions are aware of the potential risks and consequences of medical waste on their health; The results of the study also showed that there are differences in the average waste management scale according to the variable: (the surrounding environment) in the subject of the study.